Mining Geology - Relations of the Disseminated Copper Ores in Porphyry to Igneous Intrusives - W. H. Emmons (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
This paper is the third of a series treating of the relations of ores of the metals to igneous rocks. The first' outlined the general problem; the second2 proposed a classification of lode ores, and showed how the distribution of the deposits is in a certain measure controlled by the contour of the roof of the parent batholith. A number of mining districts were discussed, the examples being selected chiefly from group 2 of the classification. The proposed classification of lode deposits, briefly stated, is as follows: 1. Cryptobatholithic: near hidden batholiths which have not yet been exhumed by erosion. 2. Acrobatholithic: in and near cupolas or domes of batholiths—the high points of larger underlying masses. 3. Epibatholithic: on batholiths, near their rims, but below eroded cupolas, or below the highest points of the roofs. 4. Embatholithic: among closely-spaced outcrops which probably are parts of a single bathohth. The outcrops of invaded rocks predominate. 5. Endobatholithic. in and near roof pendants of large batholiths. The invading rocks predominate. 6. Hypobatholithic: in deeply-eroded batholiths, where even roof pendants have been eroded. Deposits of certain metals on the roofs of the batholiths are much more numerous in some positions than deposits of other metals, and the horizontal zonal arrangements of lodes of different metals are shown characteristically only in certain groups. In a large measure, also, the character of the fracturing and metallization is determined by the position on the roof of the batholith. The disseminated copper ores in porphyry constitute a clearly-defined type. All the deposits of these ores, as far as known, are in group 2. They appear to have been formed only in and around small upward projections of the parent granitic masses, and not low on the walls of the